Inventarisasi Aset Berdasarkan Peraturan Menteri Dalam Negeri Republik Indonesia Nomor 47 Tahun 2021 – Sebuah Studi Kasus - Rosmiati, Mia; Anggrani, Berina (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Local governments have the authority to manage regional finances, including managing their public assets. One of the stages in the management of public assets is administration which consists of bookkeeping, inventory, and reporting of regional property. The inventory is carried out in order to produce useful information for the presentation of financial statements and as a basis for making policies for the management of regional property. In the implementation of the inventory of public assets, regional financial agencies and assets are still experiencing problems. This study aims to find out and analyze the implementation of public assets inventory by the Bandung City Regional Finance and Assets Agency. This research is descriptive qualitative research. Types and sources of data are in the form of primary and secondary data. Methods for gathering data include documentation, interviews, and observation. Data reduction, data presentation, and conclusion-making are the steps in data analysis. The results of this study show that the Bandung City BKAD implements Permendagri Number 47 of 2021 concerning bookkeeping, inventory, and reporting even though it still obstacles in several aspects.